2016
DOI: 10.1103/physrevb.93.174303
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium processes from generalized Langevin equations: Realistic nanoscale systems connected to two thermal baths

Abstract: We extend the generalized Langevin equation (GLE) method [L. Stella, C. D. Lorenz, and L. Kantorovich, Phys. Rev. B 89, 134303 (2014)] to model a central classical region connected to two realistic thermal baths at two different temperatures. In such nonequilibrium conditions a heat flow is established, via the central system, in between the two baths. The GLE-2B (GLE two baths) scheme permits us to have a realistic description of both the dissipative central system and its surrounding baths. Following the ori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 109 publications
(202 reference statements)
0
25
0
Order By: Relevance
“…In Ref. [61], we have shown that depending upon the value used for such parameters, one can obtain completely different physical results. In the present work, we want to study exclusively the influence of the length of the system and the baths' temperatures on the thermal transport properties.…”
Section: Methods and Systemsmentioning
confidence: 99%
See 4 more Smart Citations
“…In Ref. [61], we have shown that depending upon the value used for such parameters, one can obtain completely different physical results. In the present work, we want to study exclusively the influence of the length of the system and the baths' temperatures on the thermal transport properties.…”
Section: Methods and Systemsmentioning
confidence: 99%
“…In a recent paper [61], we have discussed the advantages of the GLE-2B approach over other more conventional thermostatting approaches such as Nose-Hoover or simple Langevin thermostats. Here, we use our GLE-2B approach as it does not rely on the use of adjustable parameter(s) to describe the relaxation processes in the baths.…”
Section: Methods and Systemsmentioning
confidence: 99%
See 3 more Smart Citations